Measuring Beliefs in Conspiracy Theories: Developing the Turkish Conspiracy Mentality Scale (TCMS) - Nuh Akçakaya; Abdullah Koçak (Journal of Economy Culture and Society)
Scales that claim to measure generic conspiracy beliefs are significant instruments for understanding people’s tendency to believe in specific conspiracy theories. Several studies have been conducted on conspiracy theories in Türkiye in recent years. However, there is a lack of a scale that measures generic conspiracy beliefs and a scale that can be developed by considering the local socio-cultural dynamics of Türkiye. This study aims to develop a psychometrically valid and reliable Turkish scale for assessing generic conspiracy beliefs. This study introduces the Turkish Conspiracy Mentality Scale (TCMS), which was developed to measure generic conspiracist beliefs and predict specific theory endorsements. The validity and reliability of the scale were evaluated with reference to three studies. Study 1 (N=112) explored four critical dimensions of conspiracy: deep state, sexuality, foreign powers, and health. Study 2 (N=374) confirmed the content, face, criterion, predictive, and construct validity and reliability of the scale, while Study 3 (N=1110) provided further evidence of the psychometric strength of the scale in a representative Türkiye sample. A recent study conducted in NUTS 1 regions has shown that the scale can be used in a large and representative sample. The findings of this study highlight the power of TCMS in measuring and predicting generic and specific conspiracy theory beliefs.